2016
DOI: 10.1186/s40729-016-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, 12-month controlled trial to evaluate non-inferiority of early compared to conventional loading of modSLA implants in single tooth gaps

Abstract: BackgroundThe aim of the study was to evaluate whether early loading of implants with a chemically modified sandblasted, large-grit, acid-etched (SLA) (SLActive®) surface was non-inferior to conventional loading in terms of change in crestal bone level.MethodsThis was a randomized, controlled, multicenter study. Patients requiring single-tooth rehabilitation in the posterior maxilla or mandible received implants and were randomized to receive a provisional restoration in occlusal load after 25 ± 3 days (early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Slotte et al assessed patient satisfaction on the basis of a non-specific questionnaire, which was filled in by the patients on completion of the treatment [34]. In turn, when describing patient satisfaction following treatment Dard M. et al observed that in cases of shorter treatment duration due to earlier implant loading patients had a more positive view of their experience than patients whose treatment followed the standard procedure [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Slotte et al assessed patient satisfaction on the basis of a non-specific questionnaire, which was filled in by the patients on completion of the treatment [34]. In turn, when describing patient satisfaction following treatment Dard M. et al observed that in cases of shorter treatment duration due to earlier implant loading patients had a more positive view of their experience than patients whose treatment followed the standard procedure [24].…”
Section: Discussionmentioning
confidence: 99%
“…[17]201477posterior maxilla and mandiblePFM and provisional crownsone-stage240100Held et al [18]201334posterior maxilla and mandiblePFM crownstwo-stage16197Hicklin et.al. [19]201520posterior maxillaprovisional crownstwo-stage60100Hinkle et al [20]201424posterior maxilla and mandibleprovisional crownsone-stage12196Le Gac et al [21]20151337maxilla and mandibleall Typesone- and two-stage24–60799.5Liaje et al [22]201323maxilla and mandiblePFM crownsone-stage120100Yu et al [23]201620maxillaPFM crownsone-stage120100Hadzik et al [11]201716mandiblePFM crownstwo-stage90;Dard et al [24]201675maxilla and mandiblePFM crownstwo-stage120100Allen et al [25]201620maxillaPFM crownstwo-stage240100Al-Nawas et al [26]2012160mandiblelocatorsone-stage12398Calvo-Guirado et al [27]201640mandiblePFM crownstwo-stage12197.5Ganales et al [28]2008383maxilla and mandiblePMF crowns, composite on metal...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental implant-supported protheses 20,[35][36][37] have been developed to restore missing teeth. They are highly successful with low complication rates, influenced by various factors such as periodontal and medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The key to success with dental implants is proper osteointegration which normally takes several weeks of healing. Some studies 35,36 indicated that there was little difference in clinical outcomes with conventional loading versus early loading, but not all clinicians achieved the same results 35 . And immediate loading in the maxillary anterior region was known to have a higher failure rate compared to conventional loading, which could result in an increase in treatment time and cost and dissatisfaction of the patient and dentist 23 .…”
Section: Discussionmentioning
confidence: 99%